2017
DOI: 10.21614/chirurgia.112.6.705
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iloprost in the Healing of Colonic Anastomosis in Rats under Chemotherapy with Irinotecan

Abstract: RezumatScop: Am investigat posibilele efecte pozitive ale iloprostului în vindecarea anastomozelor colonice, la şobolani sub chimioterapie intraperitoneală cu irinotecan. Metodă: Patruzeci de şobolani masculi Wistar au fost împărţiţi în patru grupuri. În fiecare caz s-a practicat o colectomie parţială segmentară cu anastomoză termino-terminală. Ulterior li s-a administrat intraperitoneal, ser fiziologic (grupul 1), irinotecan (grupul 2), iloprost (grupul 3), irinotecan şi iloprost (grupul 4). Etapele următoare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These agents can inhibit the activity of fibroblasts and decrease the deposition of collagen, which can reduce the mechanical strength of the anastomoses [28]. Moreover, intraoperative chemotherapy can suppress the process of vascularization, promote oxidative stress, and enhance the inflammatory response, which can contribute to anastomotic tissue necrosis [29,30]. Surgeons need to carefully evaluate the risks of AL for patients before conducting this treatment.…”
Section: Gastroenterology Research and Practicementioning
confidence: 99%
“…These agents can inhibit the activity of fibroblasts and decrease the deposition of collagen, which can reduce the mechanical strength of the anastomoses [28]. Moreover, intraoperative chemotherapy can suppress the process of vascularization, promote oxidative stress, and enhance the inflammatory response, which can contribute to anastomotic tissue necrosis [29,30]. Surgeons need to carefully evaluate the risks of AL for patients before conducting this treatment.…”
Section: Gastroenterology Research and Practicementioning
confidence: 99%
“…Inflammation plays a central role in the regulation of anastomotic healing. In the inflammatory phase, white blood cells are involved in the mobilization and activation of fibroblasts and epithelial cells [13]. Chemotactic agents, cytokines and inflammatory cells are concentrated in the anastomotic area from the second postoperative day [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a series of animal experiments have also indicated that intraoperative intraperitoneal chemotherapy could bring detrimental effects on the intestinal anastomosis by increasing the inflammatory reaction, promoting oxidative stress, and reducing neoangiogenesis at the anastomotic site. These effects were observed in almost all the antitumor agents commonly used in intrapertoneal chemotherapy, including mitomycin C, cisplatin, oxaliplatin, 5-fluorouracil, iritotecan, and doxorubicin[32,36,37]. Moreover, the combination use of different chemotherapeutic agents showed enhanced negative effects on the healing process of intestinal anastomoses compared to those receiving only one type of agent[38].…”
Section: Discussionmentioning
confidence: 99%